Involvement of neutrophil hyporesponse and the role of toll-like receptors in human immunodeficiency virus 1 protection (2023)
Neutrophils contribute to pathogen clearance through pattern recognition receptors (PRRs) activation. However, the role of PRRs in neutrophils in both HIV-1-infected [HIV-1(+)] and HIV-1-exposed seronegative individuals (HESN) is unknown.